Formação profissional e identidade no serviço social : um olhar através do estágio - Souza, Rossana Lopes Pereira de (2015)
This dissertation analyzes the expansion of Brazilian high education and its inferences in the Social Work’s Formation Project, have as main theme the discussion of identitarian construction process of newly graduated social workers, from the perspective of the formation influences, in particular internship contributions. It’s proposed to meet, listen and give voice to these subject exponsing their disquiets, certainties and anxieties in relation to the profession. This study consisted of a qualitative research, of exploratory character and based on dialectic-critical theoric referencial. Its general objective is analyze which formation impacts in the construction of newly graduated professional identitarian of the social work course, be aimed at contribute for discussion about qualification in professional formation, allowing yourself to talk about what sometimes bothers, unsettles and clutters. As for the technical procedures, has chosen the document research, bibliographic and semi-structured interview. For information analysis, used the Bardin Content Analysis.